The influences of different stocking densities on some welfare indicators, lipid peroxidation (MDA) and antioxidant enzyme activities (GSH, GSH-Px, CAT) in broiler chickens - Simsek, Ulku Gulcihan; Dalkilic, Bestami; Ciftci, Mehmet; Yuce, Abdurrauf (My University, 2009)
This study was conducted to investigate the influence of stocking density on some welfare indicators, hpid peroxidation and antioxidant enzyme activities. A total of 1600 Ross-308 3 days old broiler chicks was placed into 25 floor pens (2×2 m) including five replicates from each treatment. Stocking density treatments were 22.5 (47.3 kg bw m-2), 18.75 (41.9 kg bw m-2), 15 (34.3 kg bw m-2), 11.25 (26.7 kg bw m-2), 7.5 (18.1 kg bw m-2) broilers m-2. Data on welfare indicators (litter moisture, hock and food-pad necrosis) and MDA, GSH, GSH-Px, CAT levels were determined on day 42. Body temperature was measured on days 21 and 42. Pen temperature was measured daily during 4-42 days. Higher stocking density increased litter moisture, food-pad and hock necrosis percentages (p<0.01). The body temperature of 21st day was found to be similar among the treatments (p>0.05), but it reduced significantly parallel to increasing stocking density on day 42 (p<0.01). Higher stocking density increased the pen temperature during 22-35 days (p<0.05) and 36-42 days (p<0.01), but not during 4-21 days (p>0.05). Crowding increased serum MDA level (p<0.01) and reduced GSH-Px (p<0.01), but not changed serum CAT (p = 0.07) and GSH (p = 0.28) levels. Consequently, the increase of stocking density affected badly on broiler welfare and oxidative stress parameters. © Medwell Journals, 2009.
Keywords: Antioxidant enzyme activities; Broiler; Chickens; MDA; Stocking density; Welfare